The determination of factors associated with smoking habits in pregnant women (1995)
Smoking during pregnancy can produce severe damage to the fetus. It is known the habit is more frequent in older, multiparous, nonmarried and lower education level mothers. A pilot study to define the prevalence of smoking during pregnancy and to describe the associated factors. 50 pregnant women at the Hospital de San Jose in Bogota, Colombia were surveyed about smoking habit, demographic variables and knowledge of nocives effects in the fetus. The t test was used to compare proportions and means. The 14% of the patients smoked and six out of seven stoped the habit during the pregnancy. The group of smokers had a higher age mean (p = 0.011) and all the nonsmokers were married (p = 0.013). To develop this study will help to increase the knowledge about this important problem in public health.